Challenges and recommendations to improve institutional review boards' review of community-engaged research proposals: A scoping review. Issue 1 (31st March 2023) - Onakomaiya, Deborah; Pan, Janet; Roberts, Timothy; Tan, Holly; Nadkarni, Smiti; Godina, Marina; Park, Jo; Fraser, Marilyn; Kwon, Simona C.; Schoenthaler, Antoinette; Islam, Nadia
Abstract: Academic and community investigators conducting community-engaged research (CEnR) are often met with challenges when seeking Institutional Review Board (IRB) approval. This scoping review aims to identify challenges and recommendations for CEnR investigators and community partners working with IRBs. Peer-reviewed articles that reported on CEnR, specified study-related challenges, and lessons learned for working with IRBs and conducted in the United States were included for review. Fifteen studies met the criteria and were extracted for this review. Four challenges identified (1) Community partners not being recognized as research partners (2) Cultural competence, language of consent forms, and literacy level of partners; (3) IRBs apply formulaic approaches to CEnR; & (4) Extensive delays in IRB preparation and approval potentially stifle the relationships with community partners. Recommendations included (1) Training IRBs to understand CEnR principles to streamline and increase the flexibility of the IRB review process; (2) Identifying influential community stakeholders who can provide support for the study; and (3) Disseminating human subjects research training that is accessible to all community investigator to satisfy IRB concerns. Findings from our study suggest that IRBs can benefit from more training in CEnR requirements and methodologies